2016
DOI: 10.21577/0103-5053.20160307
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of N,O-Type Inherently Chiral Calix[4]arenes Substituted on the Lower Rim and their Organocatalysis Properties

Abstract: This work presented the first study of organocatalytic behaviors of inherently chiral calix [4] arenes substituted at the lower rim. A pair of N,O-type enantiomers based on inherently chiral calix [4]arenes substituted at the lower rim were readily synthesized and applied to catalyze Henry reaction between aromatic aldehydes and nitromethane. Their organocatalytic reaction can afford the desired products in excellent yields (up to 99%) but poor enantioselectivities (up to 7.5% ee).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…But their use in asymmetric organocatalysis hasn’t been reported. To explore the organocatalytic behaviors of inherently chiral calix[4]arenes modified at the lower rim, Li et al reported the synthesis of N,O -type enantiomers based on inherently chiral calix[4]arene ( Scheme 5 ) [ 41 ]. The synthetic sequence starts from a pair of optically pure inherently chiral calix[4]arene diastereomers 16a/16b and contains four steps to lead 20a/20b as a pair of enantiomers.…”
Section: Reviewmentioning
confidence: 99%
“…But their use in asymmetric organocatalysis hasn’t been reported. To explore the organocatalytic behaviors of inherently chiral calix[4]arenes modified at the lower rim, Li et al reported the synthesis of N,O -type enantiomers based on inherently chiral calix[4]arene ( Scheme 5 ) [ 41 ]. The synthetic sequence starts from a pair of optically pure inherently chiral calix[4]arene diastereomers 16a/16b and contains four steps to lead 20a/20b as a pair of enantiomers.…”
Section: Reviewmentioning
confidence: 99%
“…The crude residue was loaded directly onto a silica gel column and purified by flash chromatography. The absolute configurations of all products were determined by comparing the retention time from HPLC data on the products with those in the literature data …”
Section: Methodsmentioning
confidence: 99%
“…[16] However, calixarene-derived PTCs for asymmetric Henry reaction is virtually absent in the literature. To the best of our knowledge, the only reported examples pertaining to calix [4]arene functionalized organocatalysts for Henry reaction are reported with poor enantioselectivities by Ma [17] (7.5 % ee) and Li [18] (22.3 % ee). Hence the design of effective PTCs for Henry reaction with high enantioselectivity under mild conditions remains the sine qua non to date.…”
Section: Introductionmentioning
confidence: 99%